The CPC: a multimedia tool to identify pests - Bal, Amadou; Brunt, Julia (Technical Centre for Agricultural and Rural Cooperation, 2003)
In several countries in Africa, a multimedia tool called the Crop Protection Compendium (CPC) is helping farmers to recognize and control crop diseases and pests via the Internet and CD-ROM.